Culinary tourists’ motivations for local food consumption in Portugal - Moura, Ana Isabel Pinto (2021)
Culinary tourism is becoming an emergent alternative to mass tourism. In the literature, different motivations have been recognized to affect the choice of tourists to experience local food. Taking this into consideration, the purpose of this study is to understand the motivational factors that lead to the consumption of local food and beverages in the geographical setting of Portugal. To test this, a modified version of Kim and Eves (2012) motivational scale was used. Data was collected via an online survey from domestic and international tourists who have been to Portugal in the past, and 190 responses were obtained, from which 162 were considered valid. The data were analysed using the statistical software IBM SPSS, and multivariate regression analysis was used to determine if the seven variables in question influenced the frequency of consumption of local gastronomy in Portugal. The results revealed that cultural experience, excitement, interpersonal relationships, sensory appeal, health concerns and prestige are all motivational factors that lead to the consumption of local food, while social and environmental sustainability is not found to motivate tourists. The present study has interesting implications for managers and marketers working within the food and tourism industry.